Hyaluronic Acid-Ceramide-based Liposomes for Targeted Gene Delivery to CD44-Positive Cancer Cells - Mallick, Sudipta; Park, Jung Hyun; Cho, Hyun-Jong; Kim, Dae-Duk; Choi, Joon Sig (Bulletin of the Korean Chemical Society, 2015)
Hyaluronic acid–ceramide (HACE)‐modified liposomes were designed using 1,2‐dioleoyl‐sn‐glycero‐3‐phoshphoethanolamine (DOPE) and 1,2‐dioleoyl‐3‐trimethylammonium‐propane (DOTAP) for targeted delivery of therapeutic genes to the CD44 receptor‐overexpressing cancer cells. Liposomes were prepared with different molar ratios of HACE; the most efficient formulation was tested for further in vitro experiments. The size and zeta potential of HACE‐based liposomes were characterized by a Zetasizer. Lipoplex was then prepared at different nitrogen/phosphate (N/P) ratios; the gel retardation test showed strong DNA‐binding affinity of liposomes for targeted gene delivery. Cytotoxicity of liposomes was evaluated by colorimetric assay (WST assay) for different cell lines such as MDA‐MB‐231 and NIH3T3 cells. HACE liposomes showed negligible cytotoxicity both in MDA‐MB‐231 and NIH3T3 cells that endow them for further therapeutic studies. We then examined the transfection efficiency of liposomes using luciferase reporter plasmid DNA. We found transfection efficiency of HACE‐based liposomes was remarkably higher in case of MDA‐MB‐231 cells as compared to NIH3T3 cells. This result was indicative for higher receptor‐binding endocytosis uptake of HACE liposomes and subsequent transfection in CD44 receptor‐positive cell lines. Our findings have shown interesting prospective for tumor‐targeted delivery of therapeutic gene in CD44 receptor‐positive cells with less cytotoxic effects.